Development of a Peer Teaching-Based Training Marketplace Platform To Improve Student Skills - Laksono, Bayu Adi; Hamdan, Ahmad; Darusman, Yus (Lembaran Ilmu Kependidikan, 2023)
This research aims to develop a peer teaching-based training marketplace application that can enhance the skills of Community Education students at the Faculty of Education, Universitas Siliwangi. The research method used is the Four D Model, which consists of Define, Design, Develop, and Disseminate phases. The Define phase involves data collection and gathering information about the issues and needs faced by Community Education students at the Faculty of Education, Universitas Siliwangi. Subsequently, in the Design phase, the design of the peer teaching-based training marketplace application is created, involving various experts and specialists in the field. The Develop phase entails the actual development and construction of the peer teaching-based training marketplace application. The application is equipped with features to facilitate knowledge and skill-sharing among students, such as discussion forums, course selection, and an assessment system. The final phase, Disseminate, involves testing the application with Community Education students at the Faculty of Education, Universitas Siliwangi. This research aims to contribute to the development of education in Indonesia, particularly in enhancing the skills of Community Education students at the Faculty of Education, Universitas Siliwangi. The peer teaching-based training marketplace application developed in this research can serve as an alternative for students to improve their skills and deepen their understanding of their respective fields.